USE OF MULTILITERATION LEARNING MODELS IN READING COMPREHENTION IN CLASS V ELEMENTARY SCHOOL: (Quasi Research Experiments on Class V Students of Trajaya III Elementary School Palasah Subdistrict Majalengka Regency) (International Conference on Elementary Education, 2018)
This study aims to determine the effect of multiliteration learning models on improving students' reading comprehension skills. This research was carried out by Trajaya III Elementary School, Palasah Subdistrict, Majalengka Regency, from January to April 2018. This study used a quasi-experimental method with the Nonequivalent Pre-Test and Post-Test Control Groups Design. The instrument used is a Process Worksheet (LKP) to measure the level of students' reading comprehension skills. The results showed that the normality test used the Shapiro-Wilk test that the posttest of the experimental class had a significance level of 0.165 or more than 0.05, so it could be stated that the data was normally distributed. Whereas for post-control data the control class has a significance value of 0.756 or more than 0.05, it can be said that the data is normally distributed. From the results of the normality test it can be concluded that the posttest data of the experimental class and the control class obtained were normally distributed. Subsequent testing using the homogeneity test in the posttest of the experimental class and the control class obtained a significance value of 0.053. From this explanation, it can be seen that the significance value is greater than 0.05. So it can be concluded that the population has a homogeneous variant. Next the results of the t test analysis show that the significance value is 0,000. The significance value is 0.05, so it can be stated that Ho is rejected, which means that there is a significant difference between the results of the experimental class and the control class. Thus, it can be concluded that there is a significant difference in the results of the experimental class posttest learning that uses multiliteration with control classes whose learning uses conventional methods. Furthermore, by using the gaint test, based on the control class data has an average gain index of 0.28 with the criteria being. The results of the gain index have medium criteria as many as 13 students and who have low criteria as many as 11 students. The gain index of the experimental class has an average of 0.63 with medium criteria, while the control class has an average of 0.28 with low criteria. Thus, there is a difference in increasing the ability to read students' understanding of the gain index between the experimental class and the control class.